Determinants for the implementation of person-centered tools for workers with chronic health conditions: a mixed-method study using the Tailored Implementation for Chronic Diseases checklist - N. Zipfel; B. Horreh; C. T. J. Hulshof; A. Suman; A. G. E. M. de Boer; S. J. van der Burg-Vermeulen (BMC, 2021)
Abstract Background The aim was to identify the most important determinants of practice for the implementation of person-centered tools which enhance work participation for patients with chronic health conditions. Methods A mixed-method study was conducted consisting of semi-structured interviews, a focus group and a survey. Various stakeholders were involved including (representatives of) workers with chronic health conditions, insurance physicians, occupational physicians, other healthcare professionals, researchers, employers, and policymakers. The semi-structured interviews were performed to identify implementation determinants, followed by a focus group to validate resulting determinants. To conclude, a survey was conducted to select the most important implementation determinants through prioritization by ranking the order of importance. The Tailored Implementation of Chronic Diseases checklist (TICD) was used as concept-driven coding frame for the qualitative analysis of the interviews and focus group. The self-developed survey was based on the domains of the TICD. The survey was analyzed by frequency count of first ranking of determinants per and between domains of the TICD. Results Various stakeholders participated (N = 27) in the interviews and focus group. The qualitative data retrieved yielded a list of determinants with additional in-depth themes according to the TICD. For the selection of the most important determinants, a survey with 101 respondents was conducted, consisting of occupational physicians, insurance physicians and workers with a chronic health condition. From the seven domains of the TICD, respondents emphasized the importance of taking into account the needs and factors associated with workers with a chronic health condition as this determinant ranked highest. Taking into account the individual needs and wishes of workers was mentioned to enable successful implementation, whereas stress of the workers was indicated to impede implementation. Other important determinants included 'being able to work with the tools' in terms of time and usability or 'cognitions, beliefs and attitudes of occupational and insurance physicians' to be able to use the tools. Conclusion This study identified the most important determinants from the perspective of various stakeholders involved in the implementation of client-centered tools in occupational health for workers with chronic health conditions. Furthermore, by prioritizing the most important determinants, targeted implementation strategies can be developed.